Recent Referees (Journal of Political Economy, 2018)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Johannes AbelerManuel AdelinoNikhil AgarwalAnna AizerDavid AlbouyHunt AllcottNizar AllouchDouglas AlmondMarcella AlsanJoshua AngristGabriela AntoniePeter ArcidiaconoCostas ArkolakisDavid AtkinYu AwayaEduardo AzevedoSimcha BarkaiEmek BaskerChristiane BaumeisterSascha BeckerJuliane BegenauSamuel BentolilaArthur BlouinAaron Bodoh-CreedStephane BonhommeSamuel BowlesEric BudishFiona BurligMichael CallenDennis CarltonMarco CastilloBriana ChangJudith ChevalierEric ChynJeffrey ClemensAllan Collard-WexlerPedro Dal BoSanmay DasThomas DavidoffGeoffroy de ClippelDavid de la CroixDaniela Del BocaMelissa DellDavid DemingWouter DesseinSebastian Di TellaEleanor DillonJonathan DingelHyun Soo DohDave DonaldsonThorsten DrautzburgPierre DuboisGreg DuncanUmut DurGilles DurantonPiotr DworczakZvi EcksteinLena EdlundMartin EichenbaumPhilipp EisenhauerMehmet EkmekciErik EysterRobert FeenstraFrederico FinanJonas FisherRaymond FismanChristopher FlinnAnthony FowlerMarco FrancesconiAlexander FrankelDaniel FriedmanJohn FriedmanDrew FudenbergDon FullertonEtienne GagnonJorge GarcíaJodi GardnerCecile GaubertAlessandro GavazzaTed GayerAlexander GelberHeiko GerlachDavid GillUri GneezyClaudia GoldinGary GortonPiero GottardiGene GrossmanRong HaiRobert HallChristian HansenJoseph HarringtonGlenn HarrisonPaul HealyRichard HoldenRichard HornbeckCosmin IlutJun IshiiKelsey JackRobert JensenJanna JohnsonJustin JohnsonBoyan JovanovicLoukas KarabarbounisDean KarlanKyeongbae KimPeter KlenowHenrik KlevenRalph KoijenJonathan KolstadScott KominersRachel KrantonIlan KremerMichael KremerTim LandvoigtClare LeaverSangMok LeeJacob LeshnoSteven LevittJin LiShengwu LiBarton LipmanFrancesco LippiJeremy LiseQingmin LiuKatrine LokenShelly LundbergRamon MarimonLaurent MathevetGregor MatvosJames McAndrewsBernard McSherryMarc MelitzKonstantinos MetaxoglouRichhild MoessnerFerdinando MonteStephen MorrisJack MountjoyPaulo NatenzonCharles NathansonPaul NiehausEd NosalCormac O GradaPaulina OlivaBenjamin OlkenMallesh PaiStavros PanageasAndreas ParkRonni PavanJudea PearlZhuan PeiRicardo Perez-TrugliaRyan PetersLaura PilossophHerakles PolemarchakisDina PomeranzAndrea PratDiego PugaValerie RameyStephen ReddingFrederic Robert-NicoudDavid RobinsonJonathan RobinsonPablo Robles SantamarinaMark RosenzweigJohn RustBernard SalaniePaola SapienzaTim Schmidt-EisenlohrPeter SchottSam Schulhofer-WohlKatja SeimAmit SeruRon ShacharArtyom ShneyerovAndrzej SkrzypaczErik SnowbergSebastian SoteloJon SteinssonSteven SternTodd StinebricknerJan StuhlerChad SyversonAlireza Tahbaz-SalehiFelix TintelnotPetra ToddAlexander TorgovitskyFabrice TourreFrancesco TrebbiStijn Van NieuwerburghDimitri VayanosRobert VerrecchiaAshley VissingShing-Yi WangDavid WeinsteinScott WeisbennerEric WeylChen YehBasit ZafarYves Zenou Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 126, Number 3June 2018 Article DOIhttps://doi.org/10.1086/698866 © 2018 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.